(untitled) (The Review of Diabetic Studies, 2025)
Emergency department (ED) overcrowding has emerged as one of the most critical global healthcare challenges, directly compromising patient safety, clinical quality, and physician performance. This systematic review synthesizes international evidence (2013–2024) on the relationship between ED overcrowding and patient outcomes, with a particular emphasis on the physician’s role in mitigating risks. A PRISMA-guided analysis of 52 studies revealed consistent associations between overcrowding and delayed treatment, increased in-hospital mortality, higher rates of left-without-being-seen (LWBS), and diminished patient satisfaction. Physician-led interventions—including rapid triage reassessment, escalation protocols, and hybrid nurse–physician triage—proved essential in correcting mis-triage and reducing adverse outcomes. Emerging innovations such as artificial intelligence (AI)-assisted triage, electronic health record (EHR)-integrated alerts, and tele-emergency care improved flow and surge response, yet required physician oversight to ensure accuracy and safety. University hospitals, burdened with both academic and clinical responsibilities, experience compounded overcrowding challenges. Sustainable solutions demand integrated models that combine physician leadership, predictive digital innovations, policy-level reforms, and physician well-being programs. Collectively, evidence underscores that robust physician engagement is indispensable for safeguarding patient outcomes and ensuring resilient ED operations worldwide.